Success In College Algebra: Examining Student Experiences In Corequisite College Algebra Courses - (:unkn) unknown (My University, 2023)
This descriptive case study explores undergraduate student experiences and perceptions in corequisite college algebra courses at an Arkansas university. Corequisite models enroll students in credit-bearing college algebra paired with required supplemental academic support. Current research has largely focused on pass rates or DFW rates. However there are limited studies exploring student experiences within this emerging model. Within this descriptive case study, several forms of data were collected. Students were surveyed on math anxiety and mindset at the start and end of the semester. Semi-structured interviews with two students and three instructors provided personal accounts of their challenges, beliefs, and attitudes related to the corequisite course. Classroom observations further contextualized the setting. Analysis revealed variability in impacts across students, highlighting individual differences, classroom dynamics, instructor influence, and external factors in shaping academic performance, anxiety, and mathematical mindset. The findings suggest student-centered instruction and integrated supports in the corequisite model can help foster more positive student experiences. However, effectiveness depends greatly on implementation, indicating a need for faculty development and standardized corequisite design focused on promoting engaging and collaborative learning environments to support student mastery.
Keywords: college algebra; corequiste